Self-reported and genetically predicted effects of coffee intake on rheumatoid arthritis: Epidemiological studies and Mendelian randomization analysis - Pu, Bin; Gu, Peng; Zheng, ChuRong; Ma, LiQiong; Zheng, XiaoHui; Zeng, ZhanPeng (Frontiers in Nutrition, 2022)
ABSTRACT Background and aims: Causal research concerning coffee intake and rheumatoid arthritis (RA) risk is controversial. The objective of this study was to further explore the causal relationship between coffee intake and RA risk. Methods: The 4310 participants from NHANES 2003-2006 were included in an epidemiological study to assess the association between coffee intake and RA by weighted multivariate logistic regression. The inverse variance weighted (IVW) method of two-sample Mendelian randomization(MR), employing genetic data from UK Biobank (428860 cases) of coffee intake and MR-Base platform (14361 cases and 43923 controls) of RA, was performed to estimate the causal relationship between coffee intake and RA. Results: Weighted multivariate logistic regression suggested no significant correlation between coffee intake and RA. Compared to the no-coffee group, the odds ratio for RA in the <1,1–3, ≥4 cups/day group were 1.297, 1.378, and 1.125 (P=0.204, 0.098, and 0.698, respectively). In the IVW of MR analysis, there was no causal relationship between coffee intake and RA (OR=1.47, P=0.218). Conclusion: Our study did not support a causal association between coffee intake and RA risk. However, it is necessary to consider valid information on coffee intake, including brewing method, type of coffee, and quantity, in further analysis of coffee intake and RA.